Simulação termodinâmica unidimensional, quase-estástica, para determinação do desempenho de motores Diesel, utilizando óleo Diesel e misturas de biodiesel - Clume, Sérgio Franco (2018)
In this work, we present the algorithms used for modeling of the air fresh mass trapped into cylinder and combustion gas mass, using specific polynomials developed by ANNAND e ROE (1974), for aplication in the custom discharge coefficients calculation, for inlet and exhaust valves. The fuel mass was modeled using an expression developed by MAROTEAUX e SAAD (2013), thus allowing use it with any fuel. The Levenberg-Marquardt Non-Linear Technique was used to optimize the unknown "injection duration", in order to aid the fuel mass calculation. The specific heat at constant pressure of the biofuel, based ou soybean, was calculated using the specific polynomial for biodiesel, developed by ANIKEEV et al. (2012). The algorithm was validated using statistical tools, comparing it with the experimental data of SOUZA JUNIOR (2009). using M95V AGRALE engine, four stroke, single cylinder. A Case Study using the experimental (lata of GUTIÉRREZ (2016), using MWM Aeteon 6.12 TCE engine, four stroke, six cylinders in line, the same one installed aboard the “Triunfo” Tugboat, from Brazilian Navy, operating as Diesel emergency generator, using B9 fuel, based on soybean. The simulation showed that the use of B9 is technically and financially feasible for the case studied.